Earnings Management Practice in Bangladesh - Parvin, Ruksana (International Journal of Business and Management Future, 2020)
This paper detects the existence of Earnings Management (EM) practice in Bangladesh. Total 105 manufacturing companies have been chosen from the different industrial sectors such as pharmaceuticals & chemicals, food & allied, cement, engineering, ceramics, tannery, textile & clothing, paper & printing, jute, fuel & power and miscellaneous. The well-known Beneish M score model has been used in detecting EM. The outcome shows that the percentage of non- manipulator companies is greater than manipulator companies except cement, paper & printing and jute industry. All out 39 % of manufacturing companies are likely manipulator where industry-wise pharmaceuticals & chemicals 28 % , food & allied 42%, cement 80%, engineering 42% , ceramics 0%  , tannery 33% , textile & clothing 40 % , paper & printing 100%, jute 100% , fuel & power 25 % and miscellaneous 17% of manufacturing organizations are likely to be manipulator for 2017. This paper may help the stakeholder for distinguishing between likely and non-likely manipulator companies from the different industrial sectors, making a better decision and formulating policy to reduce the likelihood of manipulation. As Beneish Model is a probabilistic model, it is not unquestionably decisive from the identification that organizations are likely manipulators.